2017
DOI: 10.1111/cge.13072
|View full text |Cite
|
Sign up to set email alerts
|

Genetic study of early‐onset Graves’ disease in the Chinese Han population

Abstract: Graves' disease (GD) is a complex autoimmune disorder in which genetic and environmental factors are both involved in the pathogenesis. Early-onset patients have a shorter exposure time to environmental factors and are, therefore, good models to help understand the genetic architecture of GD. Based on previous studies of early-onset GD, 11 single nucleotide polymorphisms (SNPs) and their related SNPs (R 2 > .6), SNPs located within a AE1-Mb region of the FOXP3 gene, and 20 validated GD-risk SNPs were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…When stratified by ethnicity, we found a positive association among Asians (OR = 1.31, 95%CI 1.04, 1.64; P = 0.02) but not among Caucasians (OR = 0.96, 95%CI 0.67, 1.37; P = 0.82), as shown in Figure 4. The leave-one-out sensitivity analysis confirmed the statistical robustness of our findings ( Table 3), and the study by Yuan et al (36) was regarded as the major source of heterogeneity, since the intra-study heterogeneity decreased from 75 to 57% after the removal of Yuan's study. No publication bias was detected (Egger's test: t = 0.63, P = 0.554; Begg's test: z = 1.00, P = 1.00).…”
Section: Rs3761548supporting
confidence: 85%
See 3 more Smart Citations
“…When stratified by ethnicity, we found a positive association among Asians (OR = 1.31, 95%CI 1.04, 1.64; P = 0.02) but not among Caucasians (OR = 0.96, 95%CI 0.67, 1.37; P = 0.82), as shown in Figure 4. The leave-one-out sensitivity analysis confirmed the statistical robustness of our findings ( Table 3), and the study by Yuan et al (36) was regarded as the major source of heterogeneity, since the intra-study heterogeneity decreased from 75 to 57% after the removal of Yuan's study. No publication bias was detected (Egger's test: t = 0.63, P = 0.554; Begg's test: z = 1.00, P = 1.00).…”
Section: Rs3761548supporting
confidence: 85%
“…Seven studies (30-32, 34-37) investigated the genetic effect of rs3761548 on the risk of GD, however, achieving inconsistent results. Four studies (32,34,35,37) reported significantly higher frequency of A allele in GD groups than control groups, while the other three studies (30,31,36) failed to replicate these positive findings. Under the random-effect model, the variant allele of rs3761548 polymorphism was associated with 25% higher risk of GD compared to reference allele in the overall population (OR = 1.25, 95%CI 1.02, 1.54; P = 0.03).…”
Section: Rs3761548mentioning
confidence: 88%
See 2 more Smart Citations
“…Several other studies have investigated the genetic background of GD in young adults (defined as age of GD onset lower than 30‐45 years), showing that certain genetic variants, such as HLA‐DRB1 , CTLA4 and PTPN22 polymorphisms, may be associated with age of GD onset . Most recently, based on the results of an analysis performed in a large cohort of GD patients, Yuan et al reported significant genetic heterogeneity between subjects with age of GD onset ≤20 and >20 years, suggesting it is reasonable to reduce the cut‐off value for the definition of early‐onset GD. However, data on the genetic risk factors in POGD are limited .…”
Section: Introductionmentioning
confidence: 99%